The labour supply effects of a partial cash-out of in-kind transfers to single mothers - Paul Bingley; Ian Walker (IZA Journal of Labor Economics, 2013)
We estimate a model of labour supply and participation in multiple cash and in-kind welfare programmes. The modeling exploits a reform that affected U.K. single mothers. In-work cash entitlements increased under this reform but eligibility to in-kind child nutrition programmes was lost for some households. When we allow for differences in the costs associated with each welfare programme we find that inwork cash and in-work in-kind transfers both have large positive labour supply effects. There is, however, a utility loss from programme participation which is estimated to be larger for the cash programme than for the child nutrition programmes. Our findings imply that the partial cash out of the in-kind transfers reduced labour supply and suggest that there may be a place in policy portfolios for in-kind programmes despite their 'inefficiency'.
Keywords: C31; C35; D12; J22; 330; Labour supply; Programme participation; In-kind transfers; Arbeitsangebot; Weibliche Arbeitskräfte; Alleinerziehende; Öffentliche Sozialleistungen; Familienleistungsausgleich; Beschäftigungseffekt; Großbritannien